2020
DOI: 10.1051/0004-6361/202038763
|View full text |Cite
|
Sign up to set email alerts
|

Supernovae Ib and Ic from the explosion of helium stars

Abstract: Much difficulty has so far prevented the emergence of a consistent scenario for the origin of Type Ib and Ic supernovae (SNe). Either the SN rates or the ejecta masses and composition were in tension with inferred properties from observations. Here, we follow a heuristic approach by examining the fate of helium stars in the mass range from 4 to 12 M⊙, which presumably form in interacting binaries. The helium stars were evolved using stellar wind mass loss rates that agree with observations and which reproduce … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 120 publications
9
66
0
Order By: Relevance
“…The final masses of our models with Z = 0.02 are in agreement with Yoon (2017) and Dessart et al (2020). The final masses and lifetimes of our Z = 0.015 models are also consistent with the Z = 0.0145 models from Woosley (2019) at masses where the WC/WO wind is unimportant.…”
Section: Comparison To Previous Stellar Evolution Modelssupporting
confidence: 80%
“…The final masses of our models with Z = 0.02 are in agreement with Yoon (2017) and Dessart et al (2020). The final masses and lifetimes of our Z = 0.015 models are also consistent with the Z = 0.0145 models from Woosley (2019) at masses where the WC/WO wind is unimportant.…”
Section: Comparison To Previous Stellar Evolution Modelssupporting
confidence: 80%
“…Spectral synthesis that distinguishes velocities of individual elements will also provide an alternative method to lift the degeneracy. Dessart et al (2020) showed that a star with no H-rich envelope explodes as a Type Ib (Ic) SN depending on its X(He) at the photosphere. According to Table 3 and Figure 3 in that work, a star with a photospheric He mass fraction X(He)  0.2 explodes as a Type Ic and X(He)  0.5 as a Type Ib SN.…”
Section: Light-curve Degeneraciesmentioning
confidence: 99%
“…Thus, these authors seem less keen to lean on the magnetar solution, even though they acknowledge that a sizeable fraction of the SE SNe might be out of reach (too bright) for their models. Woosley et al (2021) also occasionally discussed observational uncertainties, such as whether some specific SNe might have had their host extinction overestimated (see also Dessart et al 2020) or whether some are really "normal" Type Ibc SNe. They also ask whether the bolometric light curves (LCs) have been improperly assembled or if overly simplistic modeling was used to derive the amount of radioactive nickel.…”
Section: Introductionmentioning
confidence: 99%